Analisis Buku Matematika Peminatan SMA Kelas X Pada Materi Pokok Fungsi Eksponen Berdasarkan Kriteria Bell - Afifah Fatikhatul Inayah; Haeruddin Haeruddin; Asyril - Asyril (Universitas Pekalongan, 2023)
The aim of this study is to find out the suitability of exponent function subject in high school specialization math book for grade 10 based on Bell’s criteria. The research method used in this research is descriptive research. The object of the research is the suitability of exponent function subject in high school specialization math book grade 10 from Yrama Widya, Erlangga, and Tiga Serangkai edition based on Bell’s criteria. The data collection technique in this study is non-test technique using questionnaire by providing a research instrument in the form of an analysis sheet of high school specialization math book for grade 10 based on Bell’s criteria. Data collection was conducted by 3 people, namely researcher and two math teacher in order to get valid data. Furthermore, the suitability of exponent function subject in high school specialization math book grade 10 from Yrama Widya edition based on Bell’s criteria is good and then from Erlangga and Tiga Serangkai edition is very good.